Clarice Lispector: no coração do Recife (1925-1935). - Cavalcanti, Henrique Inojosa (2020)
This work aims to study the trajectory of Clarice Lispector when she lived in Recife, in the period between 1925 to 1935, considering the aspect of how she connected with the city. Thus, her experiences, her world visions, her perceptions about the city of Recife, will be taken into account. So, the objective of this work is based mainly on the perspective of how the writer, as a child, developed her appreciation for reading, writing, culture, to the point of deciding to start on a trajectory based on intellectuality. We used Clarice Lispector's own work to tell these stories, however, we also used interviews, books, photographs, periodicals, correspondences, in order to complement the reports about the writer, concerning her passage through the city of Recife in the period described. The Casa de Rui Barbosa Foundation's collections in Rio de Janeiro were also consulted. Clarice Lispector experienced Recife intensely, as a child lives, however, since she was a little girl, she moved forward, went further, wanting to learn through conversations, readings and from a very early age, also learned to write about the sensations she experienced, what helped us with the composition of this work, in terms of historiography.